Mott schottky heterojunction catalytic material and preparation method and application thereof
Patent Information
- Application Number
- CN202610731018.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-26
- Publication Date
- 2026-08-28
Smart Images

Figure CN122644103A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology, and relates to a Mott-Schottky heterojunction catalytic material, its preparation method and application. Background Technology
[0002] Hydrogen energy boasts zero carbon emissions and high energy density (approximately 282 kJ·mol⁻¹). -1 Hydrogen evolution has shown significant advantages in mitigating global carbon emissions. In electrochemical water splitting technologies driven by renewable energy sources (such as solar and wind power), the cathode hydrogen evolution reaction (HER) has become a key pathway for large-scale hydrogen production due to its efficient generation of high-purity hydrogen. However, this technology is limited by the kinetic bottleneck of the anode oxygen evolution reaction (OER)—multi-step electron transfer leads to a slow reaction rate, significantly reducing the overall energy conversion efficiency.
[0003] To overcome this limitation, researchers proposed replacing the OER with a thermodynamically more favorable anodic reaction to synergistically improve the efficiency of hydrogen production at the cathode. Among these, the sulfide oxidation reaction (SOR: S...) is a key component. 2- →S+2e - SOR is a highly promising candidate reaction. Not only does SOR have superior thermodynamic advantages over OER, but it can also convert toxic H2S or S... 2- Pollutants are converted into valuable sulfur products. Coupling HER and SOR in a single electrochemical system can simultaneously achieve energy-saving hydrogen production, sulfur-containing wastewater purification, and sulfur recovery.
[0004] Hydrogen sulfide (H2S), a major sulfur-containing byproduct of heavily polluting industries such as oil refining and natural gas processing, is listed as a key air pollutant under control due to its strong corrosiveness and high toxicity. Furthermore, sodium sulfide (Na2S) is widely used in industries such as papermaking, leather manufacturing, and petrochemicals, leading to an increase in sulfide ions (S2S) in wastewater. 2- Elevated concentrations of H2S or S pose a serious threat to human health and environmental safety. Therefore, electrocatalytic decomposition of H2S or S... 2- It is a mild yet efficient strategy that can sustainably produce clean energy while solving the problem of treating highly toxic gases in the chemical industry.
[0005] While the HER-SOR coupling technology route shows great promise, it still faces key challenges. Existing catalytic materials generally suffer from low catalytic activity, susceptibility to sulfide poisoning and passivation, and insufficient long-term operational stability when treating sulfur-containing species. Furthermore, traditional electrode fabrication processes often rely on powder coating, which suffers from drawbacks such as increased resistance due to binders and easy detachment of active materials. Therefore, there is an urgent need to develop catalytic materials and controllable preparation strategies that combine high catalytic activity, strong resistance to sulfur passivation, and excellent structural stability. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a Motter-Schottky heterojunction catalytic material constructed based on electrospinning technology. This catalytic material has excellent bifunctional HER and SOR catalytic activity, strong stability, and can achieve efficient hydrogen production and sulfide conversion in an AEM electrolyzer, thereby reducing hydrogen production energy consumption.
[0007] On one hand, the present invention relates to a method for preparing a Motterschottky heterojunction catalytic material, comprising: obtaining a precursor solution, wherein the precursor solution comprises polyacrylonitrile (PAN), Ni(NO3)2·6H2O, WCl6 and an organic solvent;
[0008] The precursor solution was electrospun to obtain a PAN / WCl6 / Ni(NO3)2·6H2O composite nanofiber membrane; The composite nanofiber membrane was pre-oxidized and carbonized to obtain a Mott-Schottky heterojunction catalytic material.
[0009] Furthermore, in the preparation method of the Mott-Schottky heterojunction catalytic material provided by the present invention, the ratio of polyacrylonitrile, Ni(NO3)2·6H2O, WCl6 and organic solvent is 2.0~3.0g:2.0~2.6g:0.35~0.45g:18~25mL.
[0010] Optionally, in the preparation method of the Motterschottky heterojunction catalytic material provided by the present invention, the organic solvent is one of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), and tetrahydrofuran (THF).
[0011] Furthermore, in the preparation method of the Mott-Schottky heterojunction catalytic material provided by the present invention, the electrospinning parameters are an applied voltage of 15~20kV and a distance of 18~25cm between the collector and the needle.
[0012] Furthermore, in the preparation method of the Mott-Schottky heterojunction catalytic material provided by the present invention, the pre-oxidation temperature is 260~300℃ and the holding time is 1.5~2.5h.
[0013] Furthermore, in the preparation method of the Mott-Schottky heterojunction catalytic material provided by the present invention, the carbonization treatment is carried out in an inert gas atmosphere.
[0014] Furthermore, in the preparation method of the Mott-Schottky heterojunction catalytic material provided by the present invention, the inert gas is argon.
[0015] Furthermore, in the preparation method of the Mott-Schottky heterojunction catalytic material provided by the present invention, the carbonization treatment temperature is 650~750℃ and the holding time is 2.5~3.5h.
[0016] On the other hand, the present invention relates to a Motterschottky heterojunction catalytic material, which is prepared by the aforementioned method for preparing the Motterschottky heterojunction catalytic material.
[0017] On the other hand, the present invention relates to the application of the aforementioned Mott-Schottky heterojunction catalytic material in at least one of the catalytic hydrogen evolution reaction or sulfide oxidation reaction.
[0018] On the other hand, the present invention relates to an anion exchange membrane (AEM) electrolysis device, comprising a cathode and an anode, wherein the material of the cathode and / or the anode comprises the aforementioned Mott-Schottky heterojunction catalytic material.
[0019] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages: The Ni-WN / CNFs catalytic material prepared in this invention possesses a unique 3D network structure. Nickel nanoparticles and tungsten nitride nanowires are uniformly embedded on carbon nanofibers, forming a Motter-Schottky heterojunction that significantly promotes electron transfer. The carbon matrix ensures structural stability and efficient charge transport. This synergistic effect enables the catalytic material to exhibit excellent dual-functional catalytic activity for both HER and SOR reactions. This catalytic material demonstrates outstanding performance in an AEM electrolyzer, achieving 500 mA·cm⁻¹ at only 1.74 V. -2 It achieves industrial-grade current density and excellent stability (negligible current decay after 72 hours of operation), with the anode product being high-purity elemental sulfur (S8), enabling sustainable sulfur resource recovery. Compared to traditional HER||OER systems, the HER||SOR coupling system of this invention significantly reduces hydrogen production energy consumption, lowering hydrogen production energy consumption to 2.28 kWh·m³. -3 Compared to traditional systems, this method reduces energy consumption by 19.14%, significantly improving energy conversion efficiency. The preparation method of this invention employs electrospinning combined with carbonization, a simple process with mild conditions, suitable for large-scale production, requiring no complex equipment, and having low preparation costs, making it suitable for industrial application. The application of this catalytic material not only achieves efficient and green hydrogen production but also simultaneously treats sulfur-containing wastewater and recovers sulfur resources, offering both environmental and economic benefits, and providing an effective way to practically combine hydrogen production with industrial wastewater treatment. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1This is a schematic diagram of the synthesis of a Mott-Schottky heterojunction catalytic material based on electrospinning technology.
[0022] Figure 2 This is an X-ray powder diffraction pattern of a Mott-Schottky heterojunction catalytic material constructed using electrospinning technology.
[0023] Figure 3 The images shown are SEM, TEM, HRTEM, and HAADF-STEM images of a Mott-Schottky heterojunction catalytic material constructed using electrospinning technology.
[0024] Figure 4 This is an EDX elemental distribution diagram of a Mott-Schottky heterojunction catalytic material constructed based on electrospinning technology.
[0025] Figure 5 This is an X-ray photoelectron spectrum of a Mott-Schottky heterojunction catalytic material constructed using electrospinning technology.
[0026] Figure 6 This is a Raman spectrum of a Mott-Schottky heterojunction catalytic material constructed using electrospinning technology.
[0027] Figure 7 This is a sulfur droplet contact angle test diagram and a schematic diagram of the SOR reaction path of a Mott-Schottky heterojunction catalyst material constructed based on electrospinning technology.
[0028] Figure 8 This section presents the electrochemical characterization of a Mott-Schottky heterojunction catalytic material constructed using electrospinning technology. In the figures, a represents the LSV curves of the two-electrode system with and without Na₂S; b represents the LSV curve of the SOR; c represents the SOR current density at different potentials; d represents the Tafel curve of the SOR; e represents the SOR stability test; f represents the LSV curve of the HER; g represents the HER Tafel curve; and h represents the HER stability test.
[0029] Figure 9 This image shows the performance testing of a HER||SOR coupled system in an AEM electrolyzer using a Motter-Schottky heterojunction catalyst fabricated using electrospinning technology. In the image, a is a schematic diagram of the apparatus; b is a comparison of the LSV curves of the HER||SOR and HER||OER systems; c shows the hydrogen production and Faraday efficiency; d is the XRD pattern of the anode product S8; e is the UV-vis spectrum of the anode electrolyte; f shows the high current density stability test; and g is a comparison of energy consumption. Detailed Implementation
[0030] The technical solution of the present invention will be described below with reference to embodiments. However, the present invention is not limited to the following embodiments. Unless otherwise specified, the experimental and detection methods described in each embodiment are conventional methods; the reagents and materials described are commercially available unless otherwise specified. Unless otherwise specified, all percentages in the following embodiments refer to mass percentages. Unless otherwise specified, all proportions in the following embodiments refer to mass ratios.
[0031] Example 1 This embodiment provides a method for preparing a Mott-Schottky heterojunction catalytic material based on electrospinning technology.
[0032] Step 1: Prepare PAN / WCl6 / Ni(NO3)2·6H2O composite nanofiber membrane; Step 1.1: Dissolve 2.5g of PAN in 20mL of DMF and stir continuously at room temperature for 1h to form a homogeneous solution; Step 1.2: Measure Ni(NO3)2·6H2O and WCl6 in a mass ratio of 8:1, with a total amount of 9 mmol, and add them to the solution in Step 1.1. Stir at room temperature for 12 hours until completely dissolved to form a homogeneous electrospinning precursor solution. Step 1.3: The precursor solution obtained in step 1.2 is loaded into a 20mL syringe and electrospun. A voltage of 18kV is applied and the distance between the aluminum foil collector and the needle is 20cm. The PAN / WCl6 / Ni(NO3)2·6H2O composite nanofiber membrane is collected. Step 2: Perform pre-oxidation and carbonization treatment on the composite nanofiber membrane obtained in Step 1; Step 2.1: The composite nanofiber membrane obtained in Step 1.3 is subjected to pre-oxidation treatment at a temperature of 280℃ and a heating rate of 5℃·min. -1 The heat preservation time is 2 hours; Step 2.2: The pre-oxidized fiber membrane is carbonized under an argon atmosphere at a temperature of 700℃ and a heating rate of 5℃·min. -1 The heat treatment time was 3 hours, and after natural cooling to room temperature, the Motterschottky heterojunction catalytic material Ni-WN / CNFs was obtained.
[0033] Comparative Example 1 For ease of comparison, a catalytic material without the addition of WCl6 was also prepared. The specific preparation method is as follows: Step 1.1: Dissolve 2.5g of PAN in 20mL of DMF and stir continuously at room temperature for 1h to form a homogeneous solution; Step 1.2: Add 9 mmol Ni(NO3)2·6H2O and stir at room temperature for 12 h until completely dissolved to form a uniform electrospinning precursor solution; Step 1.3: The precursor solution was loaded into a 20mL syringe and electrospun. A voltage of 18kV was applied and the distance between the aluminum foil collector and the needle was 20cm. The PAN / Ni(NO3)2·6H2O composite nanofiber membrane was collected. Step 2.1: The composite nanofiber membrane is pre-oxidized at a temperature of 280℃ and a heating rate of 5℃·min. -1 The heat preservation time is 2 hours; Step 2.2: The pre-oxidized fiber membrane is carbonized under an argon atmosphere at a temperature of 700℃ and a heating rate of 5℃·min. -1 The heat treatment time was 3 hours, and after natural cooling to room temperature, Ni / CNFs catalyst material was obtained.
[0034] Comparative Example 2 For ease of comparison, a catalyst material without the addition of Ni(NO3)2·6H2O was also prepared. The specific preparation method is as follows: Step 1.1: Dissolve 2.5g of PAN in 20mL of DMF and stir continuously at room temperature for 1h to form a homogeneous solution; Step 1.2: Add 9 mmol WCl6 (without adding Ni(NO3)2·6H2O), stir at room temperature for 12 h until completely dissolved, forming a homogeneous electrospinning precursor solution; Step 1.3: The precursor solution was loaded into a 20mL syringe and electrospun. A voltage of 18kV was applied and the distance between the aluminum foil collector and the needle was 20cm. The PAN / WCl6 composite nanofiber membrane was collected. Step 2.1: The composite nanofiber membrane is pre-oxidized at a temperature of 280℃ and a heating rate of 5℃·min. -1 The heat preservation time is 2 hours; Step 2.2: The pre-oxidized fiber membrane is carbonized under an argon atmosphere at a temperature of 700℃ and a heating rate of 5℃·min. -1 The heat treatment time was 3 hours, and after natural cooling to room temperature, WN / CNFs catalytic material was obtained.
[0035] Figure 1This diagram illustrates the synthesis of Ni-WN / CNFs catalytic materials. The method primarily involves two key stages. First, PAN / WCl6 / Ni(NO3)2·6H2O nanofiber membranes are prepared using electrospinning technology. Then, through two steps—pre-oxidation and high-temperature carbonization—the nanofibers are transformed into Ni-WN / CNFs composite materials.
[0036] Figure 2 The X-ray powder diffraction patterns of Ni-WN / CNFs and Ni / CNFs, WN / CNFs catalytic materials prepared by the method of this invention are shown. Analysis of the phase composition and crystal structure of the obtained catalytic materials revealed peaks at 44.3°, 51.6°, and 76.09°, characteristic of Ni XRD (JCPDS No. 89-7128). In addition to the characteristic Ni XRD peaks, characteristic WN XRD peaks (JCPDS No. 25-1256) were also observed in Ni-WN / CNFs, indicating the successful preparation of this catalytic material.
[0037] Figure 3 The images show SEM, TEM, HRTEM (see TEM image inset), and HAADF-STEM images of the Ni-WN / CNFs catalytic material prepared by the method of this invention. The images reveal a 3D network structure composed of interwoven nanofibers. High-resolution transmission electron microscopy (HRTEM) clearly shows a large number of nanoparticles (NPs) densely distributed throughout the carbon nanofibers, exhibiting distinct lattice fringes with interplanar spacings of 0.25 nm and 0.21 nm, corresponding to the (100) crystal plane of WN and the (111) crystal plane of Ni, respectively. This confirms the successful preparation of the Ni-WN / CNFs catalytic material.
[0038] Figure 4 The EDX elemental distribution diagram of the Ni-WN / CNFs catalytic material obtained by the preparation method of this invention shows that the four elements C, N, Ni and W in the Ni-WN / CNFs composite material exhibit a uniform spatial distribution, and no other elements were found, which is consistent with the results of HAADF-STEM.
[0039] Figure 5The images show the X-ray photoelectron spectroscopy (XPS) spectra of Ni-WN / CNFs and Ni / CNFs and WN / CNFs catalytic materials obtained by the preparation method of this invention. The full XPS spectrum shows that in the Ni 2p high-resolution XPS spectrum, 852.83 eV corresponds to the zero-valence state of metallic Ni, while the peaks at 857.21 eV and 874.88 eV are attributed to the 2p3 / 2 and 2p1 / 2 orbitals of Ni, respectively, with satellite peaks at 862.68 eV and 881.38 eV, respectively. Compared to Ni / CNFs, the Ni 2p3 / 2 peak in Ni-WN / CNFs is positively shifted by 0.8 eV. The high-resolution XPS spectrum of W4f can be divided into four peaks. The two characteristic peaks with higher binding energies at 37.34 eV and 35.88 eV can be attributed to W4f5 / 2 and W4f7 / 2 corresponding to the oxidation states of W, due to unavoidable oxidation from air exposure. The pair of peaks at 34.04 eV and 32.14 eV can be attributed to the WN bond in WN. High-resolution N1s spectra show two peaks at 398.05 eV and 400.68 eV. The peak at 398.05 eV is related to the NW bond, while the peak at 400.68 eV is considered to be at the tetrahedral interstitial position of N atoms in WN. The XPS spectra show a positive shift in the Ni 2p binding energy relative to Ni / CNFs, while the binding energies of W4f and N1s show a negative shift relative to WN / CNFs, confirming the migration of electrons from Ni species to WN. XPS spectral analysis clearly confirms that the formation of the Mott-Schottky heterojunction is driven by a built-in electric field, leading to charge transfer and surface electron reconstruction.
[0040] Figure 6 The Raman spectrum of the Ni-WN / CNFs catalytic material obtained by the preparation method of this invention is shown. After being reacted at open circuit potential and low potential for 10 min, the spectrum was obtained at 304 cm⁻¹. -1 The Raman signal at point S8 2- Then at 511cm -1 S4 can be observed at this location. 2- A characteristic peak. As the potential increases, a peak corresponding to S8 at 408 cm⁻¹ can be detected. -1 Based on the above results, a stepwise oxidation mechanism of SOR on Ni-WN / CNFs can be proposed.
[0041] Figure 7 The present invention provides a sulfur droplet contact angle test diagram and a schematic diagram of the SOR reaction pathway for the Ni-WN / CNFs catalytic material prepared by the present invention. To evaluate the interfacial interaction between the material and sulfur, the contact angle of Ni-WN / CNFs was measured. The contact angle of Ni-WN / CNFs was 110°, which confirms a relatively weaker interaction between Ni-WN / CNFs and sulfur. The schematic diagram of the SOR reaction pathway shows the sulfur droplet contact angle.2- The relevant mechanisms of oxidation, S 2- The oxidation process on the Ni-WN / CNFs electrode involves short-chain polysulfide intermediates (such as S2). 2- S4 2- ), ultimately generating S8. This process proves that using S 2- It is feasible to use it as an electron donor to replace the traditional oxygen evolution reaction (OER).
[0042] The Motter-Schottky heterojunction Ni-WN / CNFs catalytic material prepared in this invention can be used for efficient hydrogen evolution and desulfurization synergistic reactions in anion exchange membrane (AEM) electrolyzers, making it suitable for industrial scenarios such as sulfur-containing wastewater treatment and green hydrogen production. Hydrogen energy, as a clean energy source with zero carbon emissions, also possesses high energy density (approximately 282 kJ·mol⁻¹). -1 Hydrogen, with its advantages of wide availability and diverse utilization, is one of the core energy carriers for achieving carbon neutrality. Electrolysis of water for hydrogen production is considered an ideal pathway for large-scale production of high-purity hydrogen due to its high efficiency, environmental friendliness, and lack of additional carbon emissions. Replacing the oxygen evolution reaction (OER) with the thermodynamically superior sulfide oxidation reaction (SOR) can further reduce hydrogen production energy consumption and simultaneously treat pollutants. Most reported catalytic materials are either limited to narrow pH ranges and highly corrosive electrolyte systems, or suffer from low catalytic activity, easy passivation by sulfides, and poor stability in complex sulfur-containing wastewater environments. High concentrations of sulfur in sulfur-containing wastewater (such as wastewater from the petrochemical, papermaking, and leather industries) are a significant challenge. 2- Pollutants such as sulfur dioxide and hydrogen sulfide (H2S) pose a serious threat to the ecological environment. Meanwhile, traditional hydrogen production technologies rely on freshwater resources, highlighting the contradiction with the reality of water scarcity. Therefore, developing non-precious metal-based catalytic materials with broad adaptability, high catalytic activity, and strong resistance to sulfur passivation is of significant practical importance and application value for promoting the coordinated development of sulfur-containing wastewater resource utilization and green hydrogen energy industrial production.
[0043] The experimental conditions were as follows: a typical three-electrode system was used, with the prepared Ni-WN / CNFs as the working electrode, a graphite rod electrode as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode; all voltages relative to the RHE were converted using the following formula: ERHE = EHg / HgO + 0.059pH + 0.098V (KOH and natural seawater). The linear voltammetric scan was performed at a scan rate of 10 mV / s.
[0044] Figure 8 Electrochemical characterization of the Ni-WN / CNFs catalytic material obtained by the preparation method of this invention, wherein, Figure 8 In the figure, 'a' represents the LSV curve for the two-electrode system with and without Na₂S. Figure 8 In this context, b represents the LSV curve of the SOR. Figure 8In this context, c represents the SOR current density at different potentials. Figure 8 In this context, d represents the Tafel curve of the SOR. Figure 8 In this context, 'e' represents the SOR stability test. Figure 8 f in the figure represents the LSV curve of HER. Figure 8 In this context, g represents the Tafel curve of Her. Figure 8 In this context, 'h' represents the HER stability test. As can be seen from the image above, Figure 8 In the a-Ni-WN / CNFs, the ratio of OER (1.3V-10mA·cm) is higher. -2 It provides 10 mA·cm at a low operating potential of 0.45V to the SOR. -2 The current density. Figure 8 The Ni-WN / CNFs in b reached 10 mA·cm -2 With a current density of 0.45V, Ni-WN / CNFs require a small operating potential of 0.45V, which is significantly lower than other comparative catalysts. Figure 8 The 'c' in the figure represents the performance of Ni-WN / CNFs at three different voltages, which surpasses that of other comparative catalytic materials. Figure 8 The Ni-WN / CNFs exhibit the smallest Tafel slope in the d-phase, and this smaller Tafel slope demonstrates the superior SOR reaction kinetics. The stability of the catalytic material was evaluated using continuous chronopotentiometric measurements. Figure 8 The presence of 'e' indicates that Ni-WN / CNFs exhibit excellent long-term stability.
[0045] The HER catalytic performance of Ni-WN / CNFs was tested in an electrolyte containing 1M KOH. Figure 8 The LSV curves in f show that Ni-WN / CNFs achieve 10 mA cm⁻¹ -2 The current density exhibits an overpotential of 209 mV, which is lower than that of other comparative catalysts. Figure 8 The Tafel slope shown in g indicates that Ni-WN / CNFs have the lowest Tafel slope value, suggesting that Ni-WN / CNFs have faster reaction kinetics in 1.0 M KOH. HER stability was evaluated using constant chronopotential curves. Figure 8 The polarization curves in h almost overlap around 1000 cycles, and at the same time, Figure 8 The stable chronopotential curves recorded further illustrate the stability of the Ni-WN / CNFs catalytic material.
[0046] Figure 9 The performance test diagram of the Ni-WN / CNFs catalytic material in the HER||SOR coupling system obtained by the preparation method of the present invention is shown. Figure 9In the diagram, 'a' represents a schematic of the device, which uses Ni-WN / CNFs as the cathode and anode, respectively, and achieves synergistic coupling of hydrogen production and sulfur resource conversion through a dual-electrode system. Figure 9 In the figure, b represents a comparison of the LSV curves of the HER||SOR and HER||OER systems. Under the same voltage, the current density of the HER||SOR system is higher than that of the traditional HER||OER system, effectively overcoming the anode dynamics limitation of the traditional OER. Figure 9 In the figure, 'c' represents hydrogen production and Faraday efficiency. The hydrogen production rate in the cathode chamber of the HER||SOR system is 3.4 times higher than that of the traditional HER||OER system. The average Faraday efficiency (FEH2) of this system is as high as 95.0%, indicating that it has excellent hydrogen production performance and energy conversion efficiency. Figure 9 In the diagram, d represents the XRD pattern of the anode product S8. Figure 9 In the figure, e represents the UV-vis spectrum of the anolyte, which also confirms the multi-step oxidation pathway occurring on the surface of the Ni-WN / CNFs catalytic material. This effectively avoids the excessive dissolution of sulfur species and demonstrates the unique advantages of Ni-WN / CNFs in the SOR conversion process. Figure 9 f in the figure represents the high current density stability test. The Ni-WN / CNFs catalyst can maintain a relatively stable current density under high current density in AEMWE. Figure 9 In the graph, g represents the energy consumption comparison. The HER||SOR system reduces energy consumption by 19.14% compared to the traditional HER||OER system.
[0047] The embodiments described above are only some, not all, of the embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate preferred embodiments. All other embodiments obtained by those skilled in the art through related deductions and substitutions based on the inventive concept, without inventive effort, are within the scope of protection of the present invention.
Claims
1. A method for preparing a Mott-Schottky heterojunction catalytic material, characterized in that, include: A precursor solution is obtained, wherein the precursor solution comprises polyacrylonitrile, Ni(NO3)2·6H2O, WCl6 and an organic solvent; The precursor solution was electrospun to obtain a PAN / WCl6 / Ni(NO3)2·6H2O composite nanofiber membrane; The composite nanofiber membrane was pre-oxidized and carbonized to obtain a Mott-Schottky heterojunction catalytic material.
2. The method for preparing the Mott-Schottky heterojunction catalytic material according to claim 1, characterized in that, The ratio of polyacrylonitrile, Ni(NO3)2·6H2O, WCl6 and organic solvent is 2.0~3.0g:2.0~2.6g:0.35~0.45g:18~25mL.
3. The method for preparing the Mott-Schottky heterojunction catalytic material according to claim 1, characterized in that, The electrospinning parameters are: applied voltage of 15~20kV and distance between collector and needle of 18~25cm.
4. The method for preparing the Mott-Schottky heterojunction catalytic material according to claim 1, characterized in that, The pre-oxidation temperature is 260~300℃, and the holding time is 1.5~2.5h.
5. The method for preparing the Mott-Schottky heterojunction catalytic material according to claim 1, characterized in that, The carbonization process is carried out in an inert gas atmosphere.
6. The method for preparing the Mott-Schottky heterojunction catalytic material according to claim 5, characterized in that, The inert gas is argon.
7. The method for preparing the Mott-Schottky heterojunction catalytic material according to claim 5, characterized in that, The carbonization treatment is carried out at a temperature of 650~750℃ and a holding time of 2.5~3.5h.
8. A Mott-Schottky heterojunction catalytic material, characterized in that, The material was prepared using the method described in any one of claims 1 to 7.
9. The use of the Mott-Schottky heterojunction catalytic material of claim 8 in at least one of the catalytic hydrogen evolution reaction or sulfide oxidation reaction.
10. An anion exchange membrane (AEM) electrolysis device, comprising a cathode and an anode, characterized in that, The materials of the cathode and / or the anode include the Mott-Schottky heterojunction catalytic material of claim 8.